PERAN KEPALA SEKOLAH DALAM PENINGKATAN MOTIVASI KERJA GURU - FARISI, M. MADZHUB (Jurnal Psikologi Terapan dan Pendidikan, 2013)
ABSTRACT This research aim to know the role of headmaster in improvement of motivation of teacher proffessional job / activity in MTs YAJRI Payaman Secang Magelang, knows to effort for headmaster in improvement of motivation of teacher professional job/actifity in MTs YAJRI Payaman Secang Magelang, Research executed in MTs YAJRI Payaman Secang Magelang. Data collecting applies interview method, observation, and documentation. Result of research indicates that the role of headmaster in increasing motivation of teacher /activity is by using â system approachâ as way of thinking base, way of managing, and way of analysing school life. As leader of in an education institute of headmaster shall have wide knoledge and leadership skill. That thing need to be owned that be able to control, influences, and pushs its the subordinate in implementing duty admitedly, responsibility, efficient, and effective.The headmasterâs effort in increasing motivation of teacher job/ actifity,1) Specifies open management that is headmaster recieves suggestion, citicism emerging from all party/ other side area teacher, employee, and student.2) Headmaster applies division of duties and responsibility with the teacher to learn more comprehendingly/ its the duty and expected by the same job/activity for the agenda of reaching purpose of together.3) Headmaster braids goods relationship to all subordinates that is to teacher, this thing is done that they ready executes duty isas good as possible, fertilizes faithfulness and responsibility to leader, duty and workplace.4) Headmaster also does approach to increasing creativeness, high initiative to keep up spirits its the subordinate. 5) Headmaster does mapping of actifity program to increase motivation of teacher jo/activity.6) Headmater does observation having the character of continous and totally that is observation covering all inter alia aspect : levator skapula persona, execution of activity material and resistance.7) Headmaster does evaluations to cover evaluation to breakdown of duty and evaluation of document evidence, by the way of direct vision to duty evidence, evidence which has in executing by teacher then give input if there is mistake or less as according to criterion which in expecting. Keyword : Headmaster role, motivation of teacher job/ activity.